Digital Transformation and Adaptive Risk Management in Industry 4.0: A Conceptual Review of the Expanding Spectrum of Organizational Risk - Selvy Afrioza; Irvan Bernandita Primandanu (International Journal of Management Science and Information Technology, 2026)
The acceleration of digital transformation in the industry 4.0 era has fundamentally changed the way organizations conduct business processes, make decisions, and build competitive advantage. These changes have also broadened the spectrum of organizational risks, making them increasingly complex, interconnected, and difficult to predict. This phenomenon has created an urgent need for risk management strategies that are no longer reactive, but rather adaptive, proactive, and data-driven. The purpose of this study is to analyze the relationship between digital transformation and adaptive risk management strategies, focusing on how digitalization expands organizational risk from the operational level to the strategic, socio-technical, and systemic levels. This research uses a structured conceptual literature review that examines academic books, scientific journal articles, industry reports, and relevant policy documents, particularly those published in the last five years. Source collection was carried out through the stages of identification, selection, relevance evaluation, final document determination, and analysis using an interpretive qualitative approach and thematic analysis techniques. The results of the study indicate that digital transformation reconfigures organizational strategies, business processes, and decision-making patterns, while increasing vulnerability to risks in cybersecurity, data privacy, reputation, governance, and human resource readiness. This study confirms that organizations need adaptive risk management supported by digital leadership, data and security governance, organizational readiness, and continuous learning. The article's primary contribution lies in the formulation of an integrative conceptual framework linking digital transformation, the expansion of the organizational risk spectrum, adaptive risk management, and organizational resilience.